Yield Performance and Pest Infestation of High-Temperature Tolerant Tomato (Lycopersicon Esculentum) Lines for Year-Round Tomato Production in Bangladesh - Quamruzzaman, A. K. M.; Akter, Limu; Islam, Ferdouse (European Journal of Applied Sciences, 2022)
The study used 20 tomato lines/varieties at the Olericulture Division of the Horticulture Research Centre, BARI, Gazipur, Bangladesh during the summer season of 2021 to evaluate yield and yield-related components, as well as pest disease infestation. During the summer season, there was significant variation among the 20 tomato lines/varieties. The number of fruits per plant and single fruit weight ranged from 6.0 to 8.0 and 24.4g to 184.9g, respectively, while fruit length and diameter ranged from 2.2-11.6cm and 1.9-7.3cm, respectively. TSS ranged from 3.2 to 7.0 percent, with higher TSS contained lines being SLA-15 (7.0 percent), AVTO 1715 (6.3 percent), AVTO 1911 (6.0 percent), AVTO 1702 (5.6 percent), and SLA-05 (5.6 percent) (5.6 percent ). There was a significant difference in TYLCV infection and leaf sucking pest infestation, which ranged from 3.3–30 percent and 3.3–30 percent, respectively. Fruit yield ranged from 5.56-42.46 t/ha, with higher yielding lines being AVTO 1717, AVTO 1911, AVTO 1409, AVTO 1713, AVTO 1715, and AVTO 1921. Taking into account yield and yield contributing parameters, as well as pest disease infestation, the lines AVTO 1717, AVTO 1911, AVTO 1409, AVTO 1713, AVTO 1715, and AVTO 1921 may be selected further for developing better summer tomato varieties and inbred development.